Awareness and acceptance of menstrual cups and the factors associated with it among healthcare professionals in Wolaita Zone, South Ethiopia: institution-based cross-sectional study - Angwach Abrham Asnake; Molalegn Mesele Gesese; Natnael Atnafu Gebeyehu; Kelemu Abebe Gelaw; Yohannes Fikadu Geda (BMJ Open)
Objective To explore awareness and acceptance of menstrual cups and associated factors among healthcare professionals in Wolaita Zone, South Ethiopia.Design Institution-based cross-sectional study.Setting The current study was carried out among governmental health facilities in Wolaita Zone, South Ethiopia Regional State between 1 September and 30 September 2023.Participants Using a simple random sampling technique, 425 healthcare providers were selected. Data were collected using a self-administered, pre-tested questionnaire.Outcome measures The data were entered using Epi-data version 3.1, and after being exported, were analysed using SPSS version 25. Bivariate and multivariable logistic regression analyses were carried out to identify relevant components. An adjusted OR and a 95% CI were used to report the relationship between the covariates and the outcome variable.Results The level of awareness towards menstrual cups was 16.2% (95% CI 12.9% to 19.8%). Type of healthcare profession 5.75 (aOR=5.75, 95% CI 1.94 to 17.01), the use of broadcast media 4.40 (aOR=4.40, 95% CI 1.80 to 10.70), and social media use (aOR=3.24, 95% CI 1.53 to 6.88) were significantly associated with awareness towards menstrual cups.Conclusion The awareness of menstrual cups among female healthcare providers was incredibly low. Type of healthcare profession, broadcast media, and social media use were the main determinants of menstrual cup awareness. Therefore, both government and non-governmental organisations should focus on promoting and providing menstrual cups nationwide.